2016
DOI: 10.3390/cli4020022
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Drought Spatiotemporal Trends, Diverse Etic-Emic Perceptions and Knowledge: Implications for Adaptive Capacity and Resource Management for Indigenous Maasai-Pastoralism in the Rangelands of Kenya

Abstract: The study examined the spatiotemporal distribution of drought in the Maasai rangelands of Kenya. The implications of this distribution, in concert with the documented existing and/or projected social and biophysical factors, on critical rangeland resources in Maasai-pastoralism are discussed using an integrated approach. Participatory interviews with the Maasai, retrieval from archives, and acquisition from instrument measurements provided data for the study. Empirical evidence of the current study reveals tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Recent scholarship on pastoralism has benefitted from shifting its focus away from traditional views of pastoral economics to more modern approaches that incorporate the important links between globalization, local markets, migration, economic opportunities, and traditional pastoral livelihoods (Bollig and Lesorogol 2016;Bond 2014;Catley et al 2013;Galaty 2016;Gertel and LeHeron 2011;Jandreau and Berkes 2016;Kibet et al 2016;Mwangi 2016;Watson et al 2016). These new opportunities have subsequently generated new behavioural adaptations and economic strategies that require us to reclassify many of the livelihood tactics and approaches used by modern pastoralists we presented in Table 1.…”
Section: New Modes Of Scholarship On Pastoralismmentioning
confidence: 99%
“…Recent scholarship on pastoralism has benefitted from shifting its focus away from traditional views of pastoral economics to more modern approaches that incorporate the important links between globalization, local markets, migration, economic opportunities, and traditional pastoral livelihoods (Bollig and Lesorogol 2016;Bond 2014;Catley et al 2013;Galaty 2016;Gertel and LeHeron 2011;Jandreau and Berkes 2016;Kibet et al 2016;Mwangi 2016;Watson et al 2016). These new opportunities have subsequently generated new behavioural adaptations and economic strategies that require us to reclassify many of the livelihood tactics and approaches used by modern pastoralists we presented in Table 1.…”
Section: New Modes Of Scholarship On Pastoralismmentioning
confidence: 99%
“…Worth noting, prevailing discourses [18,19,20,31,61] are in accord vis-à-vis attributing the heightened manifestation of predominantly deleterious effects of climate change on societies to existing inadequate adaptive capacities. It must be pointed out that, most livelihood production systems practiced across the ASALs of Africa are coupled socio-ecological systems that predominantly operates under landscapes of frequent manifestation of unfavorable socialbiophysical conditions such as famines, conflicts/wars, recurrent/prolonged droughts, degraded natural resource-base [2,10,11,18,19,20,61,62,63,64,65]. These socio-ecological systems are frequently exposed, and are already highly sensitive and vulnerable to shifts in climatic conditions [18,19,20] particularly occurrences of recurrent and extreme droughts [10,11].…”
Section: Changing Climate Changing Ecoservice-interactions: Ecoservimentioning
confidence: 99%
“…Apropos these last points, the increased competition for critical rangeland resources (CRR), particularly forage and water, among Maasai's livestock, terrestrial wild vertebrate herbivores, and arable-farmers commonly observed during periods of drought [2,10] exemplify discordant sharing of the same. It must be pointed out that the recurrent and prolonged droughts that characterize the region [11] constitute an additional challenge confronting the proper operation of Maasai's livelihoods and indeed other resource-users across these rangelands.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations